An acoustical aid for the blind - WÓJCIK, Zbigniew Marcin (Archives of Acoustics, 1979)
Aids for the blind, used for far, which transform images to touch stimuli, are not faultless. The low resolution of mechanical operative systems and the elasticity of skin reduce practical usefulness of these aids. The aid which equivalently transforms optical images to acoustic signals is free from the faults mentioned above. It follows from physiological investigations of the brain that the right hemisphere of one born blind can take over a parallel analysis of optical images transferred by acoustic signals. A blind person who lost sight later in his We can re-cognize optical images transmitted by sound by way of an analysis mainly carried out by the left hemisphere of the brain. The left hemisphere usually performs a serial data analysis. The present paper discusses the transformation of optical images to cor-responding equivalent acoustic signals, and also presents a design for the electronic system of an acoustical aid. This system should become a valuable device in research, and it may also be applied practically in future.